ANALISIS SEKTOR EKONOMI UNGGULAN KABUPATEN PASAMAN SUMATERA BARAT - Irwandi, Putra - (Politeknik Bisnis Indonesia, 2024)
A region will develop through the capabilities of its superior sectors and encourage other sectors to develop. Thus, regional specificities, human resource potential, institutions and institutions, local physical resources are the main supporting factors for regional development. The existence of a superior sector provides an indication for the regional economy that the presence of a superior sector will have great potential to grow faster than other sectors in a region. This research was carried out with a quantitative descriptive approach using secondary data from BPS 2014-2022 to analyze 18 economic sectors that form GRDP using Typology Klassen, Location Question, Shift Share , DLQ analysis. Based on the results of the analysis, it is known that the average class typology analysis of sectors in Pasaman Regency is in Quadrant 3. Location question analysis which shows that these sectors are able to meet their own needs and allow for exports outside the region (LQ>1) is agriculture , forestry and fisheries, Government Administration, Defense and Social Security sectors, Water Supply, Waste Management, Waste and Recycling. The economy of Pasaman Regency as a result of Shift Share received very positive results regarding the total value of performance in the 2014-2022 period amounting to Rp. 620,447.01 and the entire sector is a priority in the future according to the DLQ analysis.